Odpowiedzi

2009-12-20T14:51:19+01:00
Xz+yz-x-y
ac-bc+a-b
x⁴+3x²-3x³-9x
x³+4x²-2x²-8x

xz-x+yz-y
ac+a-bc-b
x4+1,5x(4)-9a-3x(3)
x(3)-2x(c)-8x-2x(2)
  • Użytkownik Zadane
2009-12-20T14:52:33+01:00
Xz+yz-x-y=z(x+y)-(x+y)=(z-1)(x+y)
ac-bc+a-b=c(a-b)+(a-b)=(c+1)(a-b)
x⁴+3x²-3x³-9x=x^2(x^2+3)-3x(x^2+3)=(x^2-3x)(x^2+3)
x³+4x²-2x²-8x= x^2(x+4)-2x(x+4)=(x^2-2x)(x+4)
2009-12-20T14:55:36+01:00
Xz+yz-x-y = x(z-1) + y(z-1) = (z-1)(x+y)

ac-bc+a-b = a(c+1) - b(c+1) = (c+1)(a-b)

x⁴+3x²-3x³-9x = x²(x²+3) - 3x(x²+3) = (x²+3)(x²-3x)

x³+4x²-2x²-8x = x²(x-2) + 4x(x-2) = (x-2)(x²+4x)